10B + 17O fusion cross sections - Chan, Y. D.; Di Gregorio, D. E.; Ford, jr., J. L. C.; Gomez del Campo, J.; Ortiz, M. E.; Shapira, D. (American Institute of Physics, 1982)
Fil: Di Gregorio, D. E. Comisión Nacional de Energía Atómica; Argentina